PRESENTATION OF OSTEOMALACIA IN KOHISTANI WOMEN - Sahibzada, Ahmad Sohail; Khan, Muhammad Shoaib; Javed, Mohammed (Journal of Ayub Medical College Abbottabad, 2004)
Background: Osteomalacia is a common diagnosis in the Kohistani women presenting with aches and pains. This study was conducted to assess calcium and Phosphate levels in Kohistani women with osteomalacia. Methods: 50 diagnosed cases of Osteomalacia selected from amongst the women presenting with body aches were included in the study. History regarding age, marital status, parity, dietary habits, socioeconomic status etc was taken. Results: The median age was 23 years. 74% were married. Most of the women had 5 children (mode). Nine (18%) patients had hypocalcaemia, 10 (20%) had hypophoshatemia. Alkaline phosphatase was elevated in 13 patients (26%). Six (12%) patients were pregnant at the time. 74 % of patients belonged to the poor class. 70% of the patients drank less than 1 cup of milk per day. Body aches (100%), waddling gait (14%), proximal myopathy (12%), bone tenderness (6%) and carpopedal spasm (8%). Conclusions: We therefore conclude that in comparison with other parts of the world where individual risk factors cause osteomalacia, Kohistani population has a higher frequency of osteomalacia due to aggregation of three major factors namely lack of sunlight due to geographical location, excessive clothing blocking available sunlight and nutritional deficiency. Keywords: Osteomalacia, Body aches, Serum Calcium, Serum Phosphate, Alkaline Phosphate